New Antocha Osten Sacken (Diptera: Limoniidae) from Sichuan, China - Markevičiūtė, Radvilė; Podenas, Sigitas; Saldaitis, Aidas (Zootaxa, 2021)
The short-palped crane fly, Antocha (Antocha) pulchra Markevičiūtė & Podenas sp. nov. is described from specimens collected in Sichuan, China. Antocha (A.) quadrifurca Alexander, 1971 is reported for the first time in China through our research efforts. This article includes illustrations of distinguishing morphological features, an updated checklist, a general distribution and an identification key to species of Antocha Osten Sacken from Sichuan, China.